Thermal stability of vitamin C: Thermogravimetric analysis and use of total ion monitoring chromatograms - Juhász, Márta; Kitahara, Yuki; Takahashi, Seiji; Fujii, Toshihiro (Journal of Pharmaceutical and Biomedical Analysis, 2012)
► Thermal decomposition kinetics and shelf life of vitamin C were studied. ► TGA and EGA–Li +IAMS systems were used with non-isothermal heating. ► Vitamin C was shown to have higher thermal stability in nitrogen than in air. ► The shelf lives ( t 90%,25 °C ) estimated by TGA agreed with the values estimated by using a pyrogram. ► EGA–Li +IAMS is a reliable alternative method to TGA for thermal stability studies. The thermal decomposition kinetics and shelf life of vitamin C in nitrogen or air were studied by using thermogravimetric analysis (TGA) and evolved-gas analysis–lithium-ion attachment mass spectrometry (EGA–Li +IAMS). Arrhenius parameters obtained via TGA were reported for thermal decomposition. For vitamin C in a nitrogen atmosphere, the activation energy ( E a ) was 25.1 kcal/mol and the pre-exponential factor ( A) was 2.5 × 10 11 min −1. The kinetic parameters estimated via TGA agreed with values estimated from a pyrogram when the weight loss observed by TGA was shown to be due to gas evolution as a result of decomposition of the compound. Thermal stability was expressed by calculating the time for 10% of the vitamin C to decompose at 25 °C ( t 90%,25 °C ). The t 90%,25 °C for vitamin C obtained via TGA or EGA–Li +IAMS was higher in nitrogen (2.0 and 2.0 years, respectively) than in air (1.3 and 1.6 years, respectively). This indicates that the type of atmosphere influences vitamin C stability.